A review on bioconversion of lignocellulosic biomass to H2: Key challenges and new insights. (September 2016) - Ren, Nan-Qi; Zhao, Lei; Chen, Chuan; Guo, Wan-Qian; Cao, Guang-Li
Highlights: The features of the commonly used pretreatment methods were discussed. Hydrolysis methods assisting to achieve efficient hydrogen fermentation were reviewed. The review covers different approaches for lignocellulosic biomass conversion to H2 . Challenges and new insights on lignocellulose bioconversion to H2 were given. Abstract: With the increasing energy crisis and rising concern over climate change, the development of clean alternative energy sources is of great importance. Biohydrogen produced from lignocellulosic biomass is a promising candidate, because of its positives such as readily available, no harmful emissions, environment friendly, efficient, and renewable. However, obstacles still exist to enable the commercialization of biological hydrogen production from lignocellulosic biomass. Thus the objective of this work is to provide update information about the recent progress on lignocellulosic hydrogen conversion via dark fermentation. In this review, the most important technologies associated with lignocellulosic hydrogen fermentation were covered. Firstly, pretreatment methods for better utilization of lignocellulosic biomass are presented, at the same time, hydrolysis methods assisting to achieve efficient hydrogen fermentation were discussed. Afterwards, issues related to bioprocesses for hydrogen production purposes were presented. Additionally, the paper gave challenges and new insights of lignocellulosic biohydrogen production.